2010
DOI: 10.1016/j.fsi.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in holothurian coelomocyte populations following immune stimulation with different molecular patterns

Abstract: Echinoderms possess a variety of cells populating the coelomic fluid; these cells are responsible for mounting defense against foreign agents. In the sea cucumber Holothuria glaberrima, four different coelomocyte types were readily distinguished using morphological, histochemical and physiological (phagocytic activity) parameters: lymphocytes, phagocytes, spherulocytes and “giant” cells (listed in order of abundance). Monoclonal antibodies generated against sea cucumber tissues and one polyclonal against sea u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 54 publications
2
33
0
2
Order By: Relevance
“…Welsh found that human serum can deplete RNA virus through either the classical complement pathway component C4 or the alternative complement pathway component factor B (Welsh, 1977). Furthermore, it was reported that LPS and dsRNA could effectively increase phagocytes and phagocytic activities in coelomocytes of the sea cucumber Holothuria glaberrima (Ramírez-Gómez et al, 2010). In this study, we found that the AjBf gene expression increased significantly after LPS challenge, which was consistent with gene C3 as we reported early (Zhou et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Welsh found that human serum can deplete RNA virus through either the classical complement pathway component C4 or the alternative complement pathway component factor B (Welsh, 1977). Furthermore, it was reported that LPS and dsRNA could effectively increase phagocytes and phagocytic activities in coelomocytes of the sea cucumber Holothuria glaberrima (Ramírez-Gómez et al, 2010). In this study, we found that the AjBf gene expression increased significantly after LPS challenge, which was consistent with gene C3 as we reported early (Zhou et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that immune system of sea cucumber, Holothuria glaberrima, responds differentially to different PAMPs [22]. In the present study, dietary b-glucan and MOS showed different effects on the immune indices of A. japonicus.…”
Section: Discussionmentioning
confidence: 42%
“…The echinoderm immune system can be activated when encountering foreign molecules with pathogen-associated molecular patterns (PAMPs) including lipopolysaccharides, peptidoglycans, dsRNA, b-glucans, mannan, chitin and so on, which can be recognized and bound by pattern-recognition proteins (PRPs) [22]. The recognition and binding in turn evoke subsequent internal defense.…”
Section: Discussionmentioning
confidence: 99%
“…The highest expression level of StmGILT mRNA was found in the coelomocytes that are generally considered as the effector cells of echinoderm immune system [25]. The high mRNA expression level in coelomocytes of S. monotuberculatus implied that StmGILT may be an immune-related gene in this species.…”
Section: Discussionmentioning
confidence: 93%
“…In echinoderms, coelomocytes have been determined as the effector cells of immune system [25]. So, coelomocytes of sea cucumber were isolated and used as our target cells to explore the immune function of GILT in this study.…”
Section: Isolation and Primary Culture Of Coelomocytes From S Monotumentioning
confidence: 99%